2005
DOI: 10.1029/2004gl021746
|View full text |Cite
|
Sign up to set email alerts
|

Aerosol optical depth over the mountainous region in central Asia (Issyk‐Kul Lake, Kyrgyzstan)

Abstract: [1] Aerosol optical depth measurements over Issyk-Kul Lake acquired with the handheld sun photometer Microtops II are analyzed. Aerosol found over the mountainous region at the elevation of 1650 m above sea level resembles mostly clean background conditions. The yearly aerosol optical depth at a wavelength 500 nm $0.10 ± 0.03 is in agreement with the multi-year means from the background sites of the Aerosol Robotic Network (AERONET). Over a period of 4 years optical depth showed a seasonal pattern, with a maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 9 publications
0
18
0
Order By: Relevance
“…The maximum number of days with dust storms in Turkmenistan occurs between May and August, making up 62% of the annual total [22] . The aerosol optical depth over Issyk-Kul Lake (Kyrgyzstan) during the past four years shows an increase from May through September, which usually peaks during July [23] . Dust storms are prevalent through the high Iran-Afghanistan desert plains in summer, often associated with what has been referred to as the 'wind of 120 days', the highly persistent winds during the warm season [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The maximum number of days with dust storms in Turkmenistan occurs between May and August, making up 62% of the annual total [22] . The aerosol optical depth over Issyk-Kul Lake (Kyrgyzstan) during the past four years shows an increase from May through September, which usually peaks during July [23] . Dust storms are prevalent through the high Iran-Afghanistan desert plains in summer, often associated with what has been referred to as the 'wind of 120 days', the highly persistent winds during the warm season [24] .…”
Section: Discussionmentioning
confidence: 99%
“…The mountain chains impede the transport of the polluted air from Chu Valley in Bishkek, the capital of Kyrgyzstan, and from Almaty, a huge industrial center in Kazakhstan (Semenov et al 2005). Observations of a long-term total O 3 column (Aref 'ev et al 1995;Visheratin et al 2006), total NO 2 column (Aref 'ev et al 1995(Aref 'ev et al , 2009Ionov et al 2008), total CO column (Aref'ev et al 2013), and height mean concentrations of CO 2 (Kashin et al 2007 have been reported along with atmospheric spectral transparency observations Semenov 1994, Aref'ev et al 2008;Semenov et al 2005). …”
Section: Region Ii: Asiamentioning
confidence: 99%
“…Measurements with sun photometers, despite being rare in inland Central Asia (Klüser et al, 2015;Bayat et al, 2011), can provide column-integrated aerosol properties (Semenov et al, 2005;Bi et al, 2016;Chen et al, 2013). Additionally, vertically resolved information on aerosol optical properties are needed to thoroughly investigate radiative effects and dust-cloud interactions.…”
Section: Introductionmentioning
confidence: 99%